Security Enhancements for Mobile Ad Hoc Networks with Trust Management Using Uncertain Reasoning - Pushpa, R. Esther Raja (International Journal of Computer Sciences and Engineering, 2025)
The mobile ad hoc networks (MANETs) has a dynamic topology and open wireless medium, may leads to MANET suffering from many security liabilities. In this paper, using recent progresses in uncertain reasoning initiated from artificial intelligence community, an unified trust management scheme has been implemented that improves the security in MANETs. In the proposed trust management pattern, the trust model has two components: trust from direct observation and trust from indirect observation. In direct observation from an observer node, the trust value is derived using Bayesian inference, which is a form of uncertain reasoning. In Indirect observation, also called secondhand evidence that is obtained from neighbor nodes of the observer node, here the trust value is derived using the Dempster-Shafer theory, which is another form of uncertain reasoning. Merging these two components in the trust model can achieve more accurate trust values of the observed nodes in MANETs. Then evaluate this pattern under the situation of MANET routing protocol (OLSRv2). The simulation result shows the effectiveness of the proposed scheme. Exactly, throughput and packet delivery ratio can be improved considerably